MENINGKATKAN KEAKTIFAN BELAJAR SISWA MELALUI PENGGUNAAN MEDIA KONKRET PADA MATA PELAJARAN ILMU PENGETAHUAN ALAM DAN SOSIAL - Maya Anggraini; Sri Mulyani; Deistamalina Musa (Jurnal Genta Mulia, 2025)
This study aims to improve the learning activity of fifth grade students of SDN 1 Tatura Palu through the use of concrete media in learning Natural and Social Sciences (IPAS) with magnetic force material. The study was conducted using the Classroom Action Research (CAR) method consisting of two cycles. Data were collected through observation, tests, and interviews, then analyzed descriptively to measure the increase in student learning activity. This study involved 20 fifth grade students as subjects. Data collection was carried out by analyzing qualitative and quantitative data from observation sheets, learning activity tests, and interviews during the learning process. The success indicators were set with a target of learning activity completion of 80 percent. The results showed that the use of concrete media significantly increased student learning activity. At the pre-cycle stage, student learning activity only reached 52 percent. After the use of concrete media, learning activity increased to 70 percent in Cycle I and reached 89 percent in Cycle II. This study proves that concrete media is able to encourage student learning activity consistently, especially in aspects of active participation, student interaction, involvement in discussions, and the ability to complete tasks. These results indicate that the use of concrete media in science learning with magnetic force material is effective in increasing the learning activity of fifth grade students at SDN 1 Tatura Palu.